Digital literacy in Computing Vocational Course: considerations on the Course Pedagogical Project (Research, Society and Development, 2019)
Considering the relevance of the promotion of digital literacy in a secondary level vocational course, the aim of this study is to analyze the relationship between the aspects of digital literacy and the Course Pedagogical Project of the secondary level computing vocational course of the Federal Institute of Rio Grande do Norte (Instituto Federal do Rio Grande do Norte - IFRN). Thus, through an exploratory research, the objectives and the egress profile sections, that are part of the Course Pedagogical Project, were analyzed, considering the aspects of digital literacy proposed by Shetzer and Warschauer (2000). These aspects are communication, construction and research and they were the basis to the analysis of the computing Course Pedagogical Project. Through our analysis, it was possible to understand that the digital literacy aspectcs are still very subtle, specially on the objectives section. However, there is a lack of these aspects on the egress profile section, nevertheless this same section is highly oriented to computational literacy, presenting gaps in what regards digital literacy. We defend the idea that it is necessary to bring digital literacy practices into the egress profile, in order to guarantee the students’ participation in the society they are inserted.